JURIDICAL ANALYSIS OF THE APPLICATION OF SANCTIONS TO THE CRIMINAL ACTION OF THEFT WITH AGGRESSIONS PERFORMED BY CHILDREN VIEWED FROM THE SPPA LAW - Rifi Hermawati (Law Faculty of Universitas Bandar Lampung, 2023)
This study aim application penalty to follow criminal theft with a burden by children associated with the purpose of punishment and practice application penalty to follow criminal theft with a burden by children associated with the purpose of the law. Research results show to follow criminal theft with weighting that has threat criminal imprisonment of 7 (seven) years no could apply aligned diversion with provision Article 7 SPPA Law. However, thereby could deviate because the SPPA Law has confirmed that the application penalty criminal is effort law last (ultimate remedy) for the child. The SPPA Law puts forward the concept of restorative justice that is poured in the form of diversion. kindly assertively explained that diversion Becomes a priority in a complete case of an opposite child with the law in the SPPA Act. The child must treat differently from adults, therefore application penalty to a child is not based on retaliation, but on the interest best for the child, that application diversion looked at Becomes Street best for the child so could be spared from stigmatization or bad labeling from society. As for the differences in application penalty to follow criminal theft with burdens made by children needs to be studied from the purpose of law theory by Gustav Radbruch explained in implementation law should notice purposes of law substance with put order always a priority comes first in every judge's decision.